Health care: Can Britain learn from France? - Walter Elkan (Institute of Economic Affairs (IEA), 2003)
This paper is a brief account of how the French provide health care and why they seem so much more content with their system than Britain is with its National Health Service. But first there will be a brief examination of the reasons why our own NHS has come to be increasingly criticised. In its early days the NHS was regarded by many as a huge improvement on the patchwork of services, including the 'panel system' for employees that had preceded it, and many regarded it to be the envy of the world. But it has ceased to be so. Many patients continue to be properly and promptly cared for, but many others are not. The aim of the NHS to be "comprehensive and free at the point of use" can only be attained by keeping more and more patients waiting for ever longer. Outdated facilities are failing to be renewed and expensive drugs are being withheld. As a result, a parallel system of very expensive private medicine has developed for those who want a better service and are able to afford it - giving them the consumer choice which is denied to the majority. One consequence of the growth of private medicine is that the limited supply of doctors and nurses is constantly siphoned off into the private sector, thereby further eroding the ability of the NHS to provide a satisfactory service. This consequence is often forgotten. The present government is making Herculean attempts to restore the NHS partly by increasing expenditure on it, and partly by attempting to introduce reforms to the supply of services, especially reforms to the way hospitals are run. These attempts are beginning to bear some fruit, but for reasons to be explained later, it is doubtful if they can permanently raise the level of provision or of consumer satisfaction. (...)
Keywords: 330; Healthcare; Healthcare policy; Healthcare reform; Great Britain; France; Gesundheitswesen; Gesundheitspolitik; Gesundheitsreform; Großbritannien; Frankreich